Antiulcerogenic Effects of Unripe Fruits of Ficus racemosa Linn. - Sangameswaran, B.; Balakrishnan, B.R.; Bhaskar, V.H.; Jayakar, B. (Asian Journal of Chemistry, 2010)
The anti-ulcerogenic effect of unripe fruits of Ficus racemosa Linn was examined in gastric ulcer models induced by ethanol, 4 h pylorus ligation. 50 % Ethanolic extract of Ficus racemosa at the doses of 100 mg/kg (55.82 %, p < 0.01), 200 mg/kg (74.23 %, p < 0.01) and 300 mg/kg (87.73 %, p < 0.001) and sucralfate (Standard drug) at a dose of 250 mg/kg (84.66 %, p < 0.001) were given orally for 5 d. Unripe fruits of F. racemosa produced significant antiulcer activity in all the experimental gastric ulcer models.